2006
DOI: 10.1161/01.hyp.0000221223.23028.f1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Density Lipoprotein Cholesterol on Angiotensin II Sensitivity

Abstract: Abstract-Increased angiotensin II (Ang II) sensitivity predisposes to hypertension and plaque instability. Raised low-density lipoprotein cholesterol (LDL-c) may increase Ang II sensitivity, but evidence in humans for this effect of LDL-c is limited. In 28, healthy, nonsmoking subjects, aged 30Ϯ8 years, with familial hypercholesterolemia, we determined the difference in infusion rate of Ang II and norepinephrine required to increase systolic blood pressure by 20 mm Hg (Pd-20) after 4 weeks of placebo and fluva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Subsequently, reinfusion with Ang II attenuated the increased systolic blood pressure compared with that obtained in these patients prior to statin administration [27]. Administration of the HMG-CoA reductase inhibitor fluvastatin in patients with familial hypercholesterolemia also led to an attenuation of Ang II-induced increases in systolic blood pressure [28]. …”
Section: Hypertensionmentioning
confidence: 99%
“…Subsequently, reinfusion with Ang II attenuated the increased systolic blood pressure compared with that obtained in these patients prior to statin administration [27]. Administration of the HMG-CoA reductase inhibitor fluvastatin in patients with familial hypercholesterolemia also led to an attenuation of Ang II-induced increases in systolic blood pressure [28]. …”
Section: Hypertensionmentioning
confidence: 99%
“…Angiotensin II doses were chosen from previously published studies, which demonstrated a dose-dependent increase in arterial pressure and serum aldosterone in patients infused with angiotensin II at 0.5-8 ng/kg/min [26]. A recent study demonstrated that baseline plasma angiotensin II was doubled after angiotensin II infusion at 2 ng/kg/min whereas plasma angiotensin II increased nine-fold after angiotensin II infusion at 4 ng/kg/min in healthy individuals [27]. A twofold increase above basal plasma angiotensin II was also observed as a physiological response during stress in healthy volunteers [28].…”
Section: Response To Angiotensin II Infusionmentioning
confidence: 99%
“…In a study in rats, statin treatment reduced AVP, but the intake of sodium was not defined [19]. Our previous study showed that atorvastatin does not change ANP, BNP, Aldo, AVP, Ang II and PRC in healthy men in acute and shortterm studies [9], although plasma concentrations of Aldo, ANP, BNP and Ang II, but not PRC, were reduced in patients [20][21][22][23]. In the present study, Aldo and PRC were reduced after the addition of sodium to the diet, most likely secondary to expansion of the extracellular fluid volume.…”
Section: Discussionmentioning
confidence: 99%
“…It has not been clarified whether statins have an antihypertensive effect [13,23]. In a recent study of spontaneously hypertensive rats fed different diets, a reduction in BP was found only in the rats fed a highsalt diet, while those fed a low-salt or lipid-rich diet showed no modification of BP by statin treatment [5].…”
Section: Discussionmentioning
confidence: 99%